A decision making framework to evaluate the necessity of corporate restructuring. (2018) - Baghfeizi, Imaneddin Moradi; Rahmanseresht, Hossein; Fathi, Saeed
This paper aims at presenting a 3 × 3 matrix to determine the structure of a holding company based on the degree of diversification and parenting style. Non-conformity of structure with this framework means that a restructuring is necessary. Three hypotheses have been tested to evaluate the validity of this framework. The first two hypotheses respectively assess the association between the 'degree of diversification' and 'parenting style' with 'structural form' based on chi-square test. But to test the third hypothesis, the holding companies compliance with the framework is divided into two groups and Mann-Witni (U) test shows that there is a significant difference between their performances. Based on Sharp's index, the economic performance of the holdings which are consistent with the framework, over a period of five years, is about 11 times better than non-conformers with the framework.